The effect of special exercises associated with the power base device for tennis on learning the skill of the front and back stroke with the upper rotation of the young players aged (13-15) (Journal of the College of Basic Education, 2022)
The study aimed to prepare special exercises to force Base Ground tennis device, and then identify the effect of exercise for the associated device power base in learning some of the basic skills of the players emerging as the researcher used the experimental curriculum design the equal groups with pretest and posttest for the appropriateness of the nature of research. Was selected as the research sample and the (24) players sample was divided into two groups control group and empirical group. The curriculum included for my skills front corner and back corner with the rotation front of (33) educational unit and the number of modules during the week (2-3) units stood Module time of 90 minutes, after the implementation of the exercise for the device within the prescribed time researcher found that the device used was a way guide helped significantly in teaching the proper kinetic path of the arm striking the learner, since all tests indicated the superiority of the experimental group to the control group has reached a researcher to several recommendations including the circulation of the machine to be used as a teaching assistant in learning tennis skills being sends a thrill to be used by novices.